Potensi Tanaman Cengkeh (Syzygium aromaticum L.) dan Kayu Manis (Cinnamomum burmannii) Sebagai Antiinflamasi - Nastiti; Alfi, Tegar Fernanda; Jayanti, Tri Dewi; Aulia, Yunita; Elyawati, Tanti; Yesika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Inflammation is a biological response from the immune system that is triggered by various factors, including pathogens, physical trauma and toxic compounds. The inflammatory response acts by eliminating adverse stimuli and preparing the healing process. Therefore, inflammation is an important defense mechanism for health. The plants that can be used as anti-inflammatories are cloves (Syzygium aromaticum L.) and cinnamon (Cinnamomum burmannii) which are typical Indonesian spices which have been widely used by the public empirically as anti-inflammatories.